Promoting Physical Activity Among Adolescents: Recommendations From Correlation Research (La promoción de la actividad físicas entre los adolescentes: recomendaciones a partir de la investigación correlacional) - Paula Louise Bush; Cathy MacDonald (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. Adolescents are not meeting physical activity (PA) guidelines for health and, although there has been much PA intervention research for this age group, most studies have had only a small effect on teens’ PA. Many have observed that teenagers’ PA is determined by a complex array of intrapersonal, interpersonal, and family, school, and community environmental factors. We sought to update previous reviews of correlates of adolescent PA, focusing exclusively on modifiable correlates of adolescents’ PA to suggest avenues for PA promotion intervention design. Based on our findings from twenty studies exploring correlates among international samples of adolescents, we suggest that parent and peer PA and support of adolescents’ PA are important influencing factors to consider when designing PA promotion interventions for teenagers. Moreover, limited work suggests the potential importance of physical environment modifications.